Kinerja Keuangan CV. ARTHA MANDIRI - Mulia Inda Purwati (LPPM Universitas Adiwangsa Jambi, 2021)
This Study entitled “Financial Performance On CV. ARTHA MANDIRI. The purpose of this study were : 1. To determine the development of the Current Ratio (CR), , Cash Ratio, Total Assets Turn Over ( TATO), Fixed Assets Turn Over (FATO), Debt to Equity Ratio (DER), Net Profit Margin (NPM), Return on Investment (ROI) 2. To determine the financial performance of CV. ARTHA MANDIRI. To achieve this goal in doing the following steps : 1. See the development of the financial performance of the CV. ARTHA MANDIRI by using Liquidity Ratios, Activity Ratios, Solvabilitas Ratios and Profitability Ratios. 2. Conduct an analysis of financial performance of the CV. ARTHA MANDIRI 0f six indicators of financial ratios. Results of this study indicate that : 1. The development of each ratio is not optimal and fluctuates annually. 2. The financial performance of the CV. ARTHA MANDIRI are from year to year has fluctuate development and the achievement was not optimal, so in this case an enterprise is not able to perform its management company and obligations. For the management company, should seek to continue to maintain and repair financial performance in order tto be better in the future, by focusing more on improving Liquidity Ratios, Activity Ratios, Solvabilitas Ratios and Profitability Ratios.